The hardware implementation of binary translation algorithms in residual classes - Nikolai Ivanovich Chervyakov; Safwat Chiad Algalda (Наука. Инновации. Технологии, 2022)
Residue number systems (RNS's) and arithmetic are useful for several-reasons,it has a wideapplication in digital signal processing and provides enhanced fault tolerance capabilities. In this work we discuss the basic concept of forward conversion with respect to the two types of moduli-set, special and arbitrary. Special will be {2" - 1,2",2" +1} and {2", 22" - 1,2",2" +1} and their techniques. Arbitrary moduli sets are depends on use of look up tables.